Do Conceptual Innovations Facilitate Transformative Change? The Case of Biodiversity Governance - Hysing, Erik; Lidskog, Rolf (Frontiers in Ecology and Evolution, 2021)
This paper explores to what extent and in what ways conceptual innovations matter for biodiversity governance. A three-step analysis is employed, starting with identifying theoretical insights on how concepts matter for transformative change. These insights provide a lens for examining the academic debate on the Ecosystem Services concept and for identifying critical conceptual challenges related to transformative change. Finally, how the concept is used and valued in policy practice is explored through an empirical study of policy practitioners in Sweden. Based on this investigation we conclude that the ES concept holds important but restricted properties for transformative change. The ES concept provides new meanings in the form of economic valuation of nature, but these remain highly contested and difficult to practice; ES function as a boundary object, but poorly integrates social analysis and, in practice engages professionals, rather than resulting in more inclusive public participation; and ES function performatively by reflecting a technocratic ideal and raising awareness rather than targeting fundamental political challenges. Finally, the paper returns to the general questions of how conceptual innovations can generate transformative change and argues that in the continued work of conceptually developing the Nature's Contribution to People, researchers and practitioners need to pay close attention to interpretive frames, political dimensions, and institutional structures, necessitating a strong role for social analysis in this process of conceptual innovation.